Analysis of the influence of Doppler effect on Starlink downlink signals - Zhe LI; Weihong LIN; Wei DENG; Jianfeng YANG; Zhanyu ZHU (Tongxin xuebao)
Understanding the influence of Doppler effect on the transmission performance of the Starlink system was an important prerequisite to decipher its unique physical layer structure.To this end, firstly a Doppler effect model considering relative motion between the satellites and the earth was established, and the maximum Doppler effect parameters of the Starlink was provided.Subsequently, a signal model under Doppler effect was constructed based on the Starlink downlink time-frequency structure and parameters.Finally, time-frequency domain theoretical characteristics under Doppler effect for the three main components of the downlink signal were established.The validity of the theoretical findings is corroborated through simulations, serving as a valuable reference for research on transmission reliability in existing and future low earth orbit satellite communication systems.